Cameroon - Higher Education Technical Training Project - Mastri, Lawrence (World Bank, Washington, DC, 2012)
The Higher Education Technical Training Project's objective was to introduce, develop, and test a new and improved model of public higher technical education in Cameroon in the Institut Universitaire Technologique (IUT) Douala. If successful, the model could then be used as a basis for reforming other higher education institutions in Cameroon. The IUT Douala was among the most advanced in this process, and IDA believed that it could serve as a reference for other institutions. The project had defined eight indicators to evaluate the achievement of the development objective in establishing a new model for technical higher education. The indicators provided a measure of the involvement of the private sector and of the impact on students. Except for two indicators, which were dependent on the granting of full financial autonomy, all other indicators were fully met. Some of the lessons are as follows: (a)The development of a pilot in an institution requires an assessment of the organizational and managerial capacity of the institution to carry out the experiment. (b) Well defined qualitative indicators are crucial to help pilot the implementation process. (c) Developing a cooperative relationship with the private sector takes time. The private sector needs to be convinced that real and sustainable benefits can be gained from this cooperation. (d) Study tours by key stakeholders to countries which have undergone a similar process helps gain support for the reform and build momentum.